Menyoal Argumen Kebebasnilaian Teknologi dan Merumuskan Disiplin Ilmu Teknologi Islam - Juris Arrozy (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2021)
AbstractThe notion that technology is value-free is becoming a prevalent view amongst the technology practitioners, as depicted in the phrase “guns don’t kill people, people do”. This is inseparable from the definition of technology which has been narrowed down to a mere tools/artifacts and the shortcomings inherent in the existing human-technology interaction model. This paper aims to re-discuss to which extent the value-free argument of technology holds true. Based on the worldview analysis, it is evident that technology is in fact value-laden. A more comprehensive human-technology interaction model is additionally proposed to overcome the shortcomings of the previous models. Having proven that technology is in fact value-laden, this paper then examines how the comprehensive teaching of Islam as a worldview can provide as a basis for the discipline of Islamic technology, i.e. a discipline of knowledge which aims to formulate how the worldview of Islam serves as the foundation for the technological development and (contemporary) technology evaluation. Some topics on the worldview of Islam that are relevant to the inventor and user of technology as well as its implementation on the practical level are addressed to show the wide-ranging scope of the discipline of Islamic technology.